Surgical treatment strategies for patients with type A aortic dissection involving arch anomalies - Zhu, Jiade; Tong, Guang; Zhuang, Donglin; Yang, Yongchao; Liang, Zhichao; Liu, Yaorong; Yu, Changjiang; Zhang, Zhen; Chen, ZeRui; Liu, Jie; Yang, Jue; Li, Xin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the surgical modalities and outcomes in patients with type A aortic dissection involving arch anomalies. Method: Patients with type A aortic dissection who underwent surgical treatment at our center between January 2016 and December 31, 2020 were selected for this retrospective analysis. Data including computer tomography (CT), surgical records, and cardiopulmonary bypass records were analyzed. Peri-operatively survived patients were followed up, and long-term mortality and aortic re-interventions were recorded. Result: A total of 81 patients with arch anomalies were included, 35 with “bovine” anomalies, 23 with aberrant right subclavian artery, 22 with isolated left vertebral artery, and 1 with right-sided arch + aberrant left subclavian artery. The strategies of arch management and cannulation differed according to the anatomic variation of the aortic arch. Seven patients (9%) died after surgery. Patients with "bovine" anomalies had a higher perioperative mortality rate (14%) and incidence of neurological complications (16%). Four patients died during the follow-up period with a 6-year survival rate of 94.6% (70/74). Four patients underwent aortic re-intervention during the follow-up period; before the re-intervention, three received en bloc technique (13.6% 3/22) and one received hybrid therapy (11.1% 1/9). Conclusion: With complete preservation and reconstruction of the supra-arch vessels, patients with type A aortic dissection combining arch anomalies can achieve a favorable perioperative prognostic outcome. Patients who receive en bloc technique are more likely to require aortic re-intervention compared with patients who underwent total arch replacement with a four-branched graft vessel. Cannulation strategies should be tailored according to the variation of anatomy, but routine cannulation with the right axillary artery can still be done in most patients with arch anomalies, even for aberrant right subclavian artery patients.